Pengaruh Kecemasan Matematika terhadap Kemampuan Penalaran Matematika Peserta Didik - Nadia Lisbeth Napitupulu; Amanda Mevianti; Leonard Leonard (Journal of Instructional Development Research, 2023)
This study aims to find out about the effect of mathematical anxiety on mathematical reasoning ability. The research method used for this research is quantitative survey research at SMKN 15 Bekasi City and SMK Global Teknologi for the 2021/2022 academic year. The sample used was 100 students consisting of class X with data collection techniques using simple random sampling. Data collection was carried out using questionnaire dissemination and question tests. This research was conducted in April - August 2022. The results revealed that based on the test obtained Fcalculate = 10.6107 and Ftabel = 3.94 with a significant level of âˆ = 0.05. Because Fcalculate > Ftable, H0 is rejected which means that there is an influence between mathematical anxiety and mathematical reasoning ability.